Improving student involvement in physics statistics through e-task - Zakirman Zakirman (Jurnal Pijar Mipa, 2023)
The Open Educational Resources (OER) media is used in distance lectures in Statistical Physics to increase student learning resources. However, OER needs to support distance lectures optimally. Therefore, a case-based E-task is needed as an alternative solution. This study investigated the effect of using e-Task on student involvement in Statistical Physics lectures. This type of research is quasi-experimental. This research was conducted in semester 2021.2 at the Open University, involving a sample of students taking statistical physics courses in the Physics Education program. The data analysis technique used was the independent sample t-test, with the data being normally distributed and homogeneous. Based on the results of the independent sample t-test analysis above, it can be concluded that the experimental class has a higher score than the control class, namely the attendance percentage is 100, the discussion percentage is 80.8, and case-based e-task solving is 7.3. It shows that there is a significant difference between the experimental class and the control class. Thus the use of e-task can increase student involvement in Statistical Physics lectures.